2018
DOI: 10.1002/jin2.41
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanosuspension‐based dissolving microneedle arrays for transdermal delivery of a hydrophobic drug

Abstract: A nanosuspension (NS) was formulated from the lipophilic molecule cholecalciferol (CL) for enhanced transdermal delivery by embedding this NS into hydrophilic polymer‐based dissolving microneedles (DMNs). First, the NS was prepared by sonoprecpitation with different molecular weights of poly (vinyl alcohol) and poly (vinyl pyrrolidone) as stabilizers and using two different solvents for particle size and zeta potential optimization. DMN arrays were then prepared by centrifugation‐assisted micromoulding and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 32 publications
6
68
0
Order By: Relevance
“…This area could be reduced by increasing the drug load within the MN arrays. As vitamin B12 is only sparingly water soluble, formulating a nanosuspension prior to casting MN arrays is also a possible approach (Vora et al, 2018;McCrudden et al, 2018). Although there are considerable inherent differences between MN patches and currently marketed transdermal patches, relatively big patches are generally accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
“…This area could be reduced by increasing the drug load within the MN arrays. As vitamin B12 is only sparingly water soluble, formulating a nanosuspension prior to casting MN arrays is also a possible approach (Vora et al, 2018;McCrudden et al, 2018). Although there are considerable inherent differences between MN patches and currently marketed transdermal patches, relatively big patches are generally accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, using biodegradable polymeric micro- or nanoparticles often necessitates high amounts of polymeric excipients to encapsulate the drug. Clearly, this results in a lower drug loading in the MN arrays ( Battisti et al., 2019 ; Vora et al., 2018 ). Alternatively, a commercially available MTX free acid (MTX), which is the poorly water-soluble form of the drug could be used.…”
Section: Introductionmentioning
confidence: 99%
“…However, this poorly water-soluble drug form exists as micron-sized crystals and incorporating such drug crystals into a hydrophilic polymeric hydrogel (which forms the MN matrix) has been reported to be a challenging task, due to the difficulty of micron-sized hydrophobic drug-polymeric hydrogel mixing. This could lead to production of inhomogeneous MN with variable drug loadings ( Vora et al., 2018 ; Mc Crudden et al., 2018 , Abdelghany et al., 2019 ). Water-miscible organic solvents can be used to facilitate drug mixing with the MN polymeric matrix hydrogel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microneedles that are a few hundred micrometers in length can physically pierce the skin with minimal invasion, which enables the simple, painless, and effective delivery of active ingredients into the skin. Their applicability has been widely studied in various fields, such as cosmetics, biomedicines, and vaccines [1][2][3][4][5]. Beginning with a study [6] in which microneedles consisting of silicon were observed to increase the skin permeability of calcein, various solid microneedles (SMNs) fabricated from metal, ceramic, or glass have been reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%